Mapeamento geológico e estrutural da rocha fresca aflorante no talude leste da mina de Boa Vista, Catalão, GO - Ramires, João Eduardo Fochi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Boa Vista mine is located near the Catalão city, in the southeast portion of the Goiás State, and currently represents 7.0 to 8.0% of the world niobium production, playing an important role in the economy of Goiás and Brazil. Mining activities in the Boa Vista mine began with the mining of oxidized ore hosted in the weathering profile. The high susceptibility of the rocks from the Catalão I and II complexes to chemical weathering developed thick soil horizons, providing nearly 40 years of mining from this material. However, due to the continuous development of the pit, thick bedrock blocks (fresh rock) began to crop out in the midst of the soil cover, predominantly in the east slope of the mine. With the certainty of future scarcity of the oxidized ore mined in the weathering profile, Anglo American has developed a project called Fresh Rock Project, with the aim to improve the knowledge of the future material to be mined from the fresh rock, This B.Sc. monograph from the geology course at Unesp is,inserted in that project. The Catalão I and II Complexes contain a wide variety of mineralization, including niobium, phosphate, rare earths, vermiculite, barite, and titanium, also showing potential for other deposits such as copper, uranium, thorium and magnetite. Niobium mining was started at the Catalão I complex in the middle of 1976. The mining was later changed to the Boa Vista mine in Catalão II, which is currently operated by Anglo American Niobium Brazil Ltda. The mine is located in the southwest portion of the Catalão II complex and comprises an area of 854.321 m by 849.933 m. The current pit has a depth of approximately 300 m. The largest fresh-rock outcropping block is situated in the east slope of the mine and takes an area of ca. 14,300 m2, followed by two smaller blocks (450 m2 and 380 m2) to the south. The differential weathering developed by each lithotype, resulted in the current pit...

A mina Boa Vista localiza-se no município de Catalão, na porção sudeste do estado de Goiás e representa atualmente, de 7,0 a 8,0% da produção mundial de Nióbio, exercendo importante papel na economia do estado de Goiás e do Brasil. A atividade mineira na mina Boa Vista foi iniciada com a lavra de minério oxidado em solo. A alta susceptibilidade das rochas dos complexos de Catalão I e II ao intemperismo químico desenvolveu espessos horizontes de solo, proporcionando quase 40 anos de lavra deste material. Entretanto, em virtude do contínuo avanço da cava, espessos blocos de rocha sã (rocha fresca) passaram a aflorar em meio aos horizontes de solo, predominantemente no talude leste da mina. Com a certeza da futura escassez do minério oxidado, lavrado no perfil de alteração, a empresa Anglo American vem desenvolvendo um projeto denominado Projeto Rocha Fresca, com o intuito de detalhar o conhecimento do futuro material a ser lavrado. Nesse projeto está inserido o presente trabalho de conclusão do curso, realizado pelo estagiário de geologia João Eduardo Fochi Ramires. Os Complexos de Catalão I e II contêm uma grande variedade de mineralizações, incluindo nióbio, fosfato, terras raras, vermiculita, titânio e barita, apresentando potencial também para outros bens minerais como cobre, urânio, tório e magnetita. A mineração de Nióbio foi iniciada no Complexo de Catalão I em meados de 1976, passando posteriormente para a mina de Boa Vista no Complexo de Catalão II, a qual é atualmente operada pelo grupo Anglo American Nióbio Brasil Ltda. A mina se localiza na porção sudoeste do complexo de Catalão II e compreende uma área de 854,321 m por 849,933 m, em consequência do avanço da cava desde o início da atividade mineira na área, atualmente o pit apresenta aproximadamente 300 m de profundidade...
Keywords: Geologia estrutural; Mapeamento geologico; Petrologia; Niobio - Minas e mineração; Catalão (GO)